2021
DOI: 10.1002/bmc.5117
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons residues and the carcinogenic risk assessment to pregnant women in Nantong, China using QuEChERS method and HPLC—A pilot case study

Abstract: A high-performance liquid chromatographic method with a modified QuEChERS extraction for the determination of polycyclic aromatic hydrocarbons (PAHs) in blood serum was developed to investigate the internal exposure level and the carcinogentic toxicity contribution rate of PAHs for pregnant women in Nantong, China. Venous blood (n = 48) was collected in the local hospital and the internal exposure level of 16 PAHs and the contribution rate of carcinogenicity to pregnant women were analyzed. Among all of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Compared to other comparable studies, the concentration of p-PAHs in our study participants was significantly higher than that observed in the general population but similar to levels observed in individuals residing or working in industrial areas (Table S6). The findings from these cohort studies have demonstrated a significant association between PAH exposure levels and various diseases, including obesity, adverse birth outcomes, and hypertension, but the corresponding urine studies have shown that the daily intake is well below the risk value (Table S7). As pointed out in previous studies, , there may be a serious underestimation in the assessment of daily intake by OH-PAHs.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other comparable studies, the concentration of p-PAHs in our study participants was significantly higher than that observed in the general population but similar to levels observed in individuals residing or working in industrial areas (Table S6). The findings from these cohort studies have demonstrated a significant association between PAH exposure levels and various diseases, including obesity, adverse birth outcomes, and hypertension, but the corresponding urine studies have shown that the daily intake is well below the risk value (Table S7). As pointed out in previous studies, , there may be a serious underestimation in the assessment of daily intake by OH-PAHs.…”
Section: Resultsmentioning
confidence: 99%
“…15 Human biomonitoring enables the evaluation of chemical exposure by measuring the parent compound, its metabolites, or other exposure-related substances as biomarkers in physiological uids (e.g., blood, urine, sweat, and breast milk) and other biological bers (e.g., hair and nails). [16][17][18][19][20][21][22][23] Compared to other biouids, urine is distinguished by its simplicity of collection, abundance of metabolites, and capacity to detect imbalances in all metabolic pathways within the body. 24,25 Thus, urinary metabolites of toxic contaminants as biomarkers are increasingly used in environmental epidemiology for assessing population-related exposure.…”
Section: Introductionmentioning
confidence: 99%
“…, hair and nails). 16–23 Compared to other biofluids, urine is distinguished by its simplicity of collection, abundance of metabolites, and capacity to detect imbalances in all metabolic pathways within the body. 24,25 Thus, urinary metabolites of toxic contaminants as biomarkers are increasingly used in environmental epidemiology for assessing population-related exposure.…”
Section: Introductionmentioning
confidence: 99%